Emisija štetnih komponenata ispušnih plinova Oto-motora - Zavada, Josip; Mavrin, Ivan (Promet - Traffic&Transportation)
This paper deals with the method which makes it possible to complete an assessment of the harmful exhaust emission level of the Otto engine in different modes of operation. Thus the paper specifically reviews: idling, stationary loads, acceleration, and deceleration. The authors discuss the impact of input values in the process of assessment upon the output values. In the process, respective concentration as well as the total volume of toxic components in a given period ·have been established. The assessment is based upon a complete estimate (computation) of a cycle in the engine cylinder while the load is selected from the system of the Europe-test. The results obtained have been verified in an experiment.